Evaluation of a commodity force sensor for building a low-cost bedsore prevention mat - Kaewjamnong, Sirak; Hongwitayakorn, Apisake (Science, Engineering and Health Studies, 2021)
Bedsores are a common disease in patients who stay in the same position for a long period of time. Regular reposition must be done to prevent the problem. Accordingly, several tools are used to reduce bedsores. The Internet of Things and the machine learning technology have made it possible to make a number of smart kits using different sensors and artificial intelligence. This research evaluated the possibility of using a commodity force or pressure sensor, and the machine learning technology to build a budget-smart mat that can monitor patients and alert the caretaker to prevent bedsores. The experiment results showed that a force sensor is a potential candidate for making a smart tool that can be used to reduce bedsores for bedridden patients in hospitals or at homes.